Developing the Latent Lip Print Using Hibiscus Sabdariffa (Roselle) Extract for Morphological Pattern Analysis in Thai Population - Titichaya Meebuathong; Praew Suppajariyawat; Sirinart Chomean; Chollanot Kaset (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: A latent lip print can be important evidence, and specific substances are needed for the development of a latent lip print. However, collecting the lip print may difficult due to people who have sensitive skin with lipsticks and almost men who do not wear lipstick. Moreover, the enhancement methods of latent lip print are still lack of standardization and consistency. Aim: To develop a new staining method for the study of the lip print patterns Thai population.Method: The latent lip prints were collected from 24 males and 24 females. The ability of Roselle extract was investigated for developing latent lip prints on cigarette paper. The developed lip print was used for the morphological pattern analysis using Suzuki and Tsuchihashi’s classification criteria combined with Autodesk SketchBook. Result: The results revealed that Roselle extract exhibited potential as a staining dye for the development of latent lip prints on cigarette paper. Among the 24 males and 24 females, Type I was found to be most common and was present in 54.55% of the volunteers, followed by Types I’, II and IV (21.12%, 14.58%, and 9.03%, respectively). The least common patterns were Types III and V, each represented in 0.35% of the total volunteers. Conclusion: latent lip print could be used for study of lip print pattern by stained with Roselle extract. Moreover, a digital method using Autodesk SketchBook serves as an alternative method that provides ease in storing and identification of lip print pattern.